2021
DOI: 10.3389/fnagi.2021.707950
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Phosphorylation Is Dysregulated Within the Basocortical Circuit in a 6-month old Mouse Model of Down Syndrome and Alzheimer’s Disease

Abstract: Down syndrome (DS) is the primary genetic cause of intellectual disability (ID), which is due to the triplication of human chromosome 21 (HSA21). In addition to ID, HSA21 trisomy results in a number of neurological and physiological pathologies in individuals with DS, including progressive cognitive dysfunction and learning and memory deficits which worsen with age. Further exacerbating neurological dysfunction associated with DS is the concomitant basal forebrain cholinergic neuron (BFCN) degeneration and ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 84 publications
(144 reference statements)
1
11
0
Order By: Relevance
“…Similar to DS, in the TS mouse, these alterations are aggravated throughout life by a variety of neuropathological processes, including increased OS [ 37 , 38 , 39 ]. In fact, TS mice exhibit an oxidative and mitochondrial brain dysfunction profile similar to the one previously described in humans with DS [ 36 , 37 , 38 , 44 , 45 , 46 , 47 , 48 ]. The increase in OS in TS mice has also been related to (i) impairments of the UPS and autophagy [ 27 , 49 ], (ii) the high density of cells with a senescent phenotype [ 35 , 39 , 46 ], and (iii) the premature neurodegeneration that occurs in the brain of this model starting at the age of 6 months [ 44 , 48 , 50 ].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Similar to DS, in the TS mouse, these alterations are aggravated throughout life by a variety of neuropathological processes, including increased OS [ 37 , 38 , 39 ]. In fact, TS mice exhibit an oxidative and mitochondrial brain dysfunction profile similar to the one previously described in humans with DS [ 36 , 37 , 38 , 44 , 45 , 46 , 47 , 48 ]. The increase in OS in TS mice has also been related to (i) impairments of the UPS and autophagy [ 27 , 49 ], (ii) the high density of cells with a senescent phenotype [ 35 , 39 , 46 ], and (iii) the premature neurodegeneration that occurs in the brain of this model starting at the age of 6 months [ 44 , 48 , 50 ].…”
Section: Introductionsupporting
confidence: 60%
“…OS reported in DS results from an imbalance between ROS production and the antioxidant system response. Previous studies from our and other laboratories have demonstrated that the hippocampus of the TS mouse is particularly vulnerable to persistent OS [ 38 , 46 , 48 ]. To better understand the hippocampal OS status of adult TS mice, first, we evaluated ROS production in both groups of animals using an H2DCFDA assay on hippocampal homogenates.…”
Section: Resultsmentioning
confidence: 99%
“…Mice were weighed, anesthetized via intraperitoneal injection of ketamine (120 mg/kg body weight) and xylazine (6 mg/kg), and then transcardially perfused with phosphate‐buffered saline. After recording post‐mortem brain weight, we dissected the basal forebrain in the medial septal/ventral diagonal band region as described previously (Alldred et al, 2021) by taking an approximately 1.5 mm thick coronal section at approximately Bregma 1.35–0.26, between the rostral‐most appearance of the anterior forceps of the corpus callosum and where the anterior commissure crosses midline (Figure 6). Frontal cortex samples were collected bilaterally from directly above the basal forebrain; hippocampal, cortical, and cerebellar tissue were isolated bilaterally from the remainder of the brain.…”
Section: Methodsmentioning
confidence: 99%
“…[106][107][108] Glucuronidase Beta (GusB; Mm01197698_m1) qRT-PCR products were utilized as a control, as GusB did not show significant changes in RNA-seq data obtained from BFCNs herein or in previous analyses. 52,104,105 Negative controls consisted of the reaction mixture without input RNA. Sample data was compared with respect to PCR product synthesis for each gene tested.…”
Section: Quantitative-real Time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%